2016
DOI: 10.1016/j.jtcvs.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix fiber microarchitecture is region-specific in bicuspid aortic valve-associated ascending aortopathy

Abstract: Objective Ascending thoracic aortic aneurysm (ATAA) in patients with bicuspid aortic valve (BAV) commonly dilate asymmetrically compared with patients with tricuspid aortic valve (TAV). This discrepancy in aneurysm geometry led us to hypothesize that microarchitectural differences underlie the observed asymmetric dilatation pattern. The purpose of this study was to characterize the microarchitectural distinctions of the extracellular matrix of the 2 phenotypes with a focus on the proportion of radially oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
(53 reference statements)
3
28
0
Order By: Relevance
“…1719 In addition, it is likely that all patients with BAV have a certain degree of ascending aortopathy because they do exhibit a greater ascending aortic diameter compared with TAV patients, 1921 even when matched for variables such as sex, age, or degree or valvulopathy. 22 The distinct manifestations of BAV- versus TAV-associated aortopathy is further supported by our previous work at the tissue, cellular, and molecular levels showing distinct biomechanical properties associated with differences in extracellular matrix maturity and architecture 2327 and altered SMC response to oxidative stress 6,28 in the BAV versus TAV aortopathy.…”
Section: Discussionsupporting
confidence: 67%
“…1719 In addition, it is likely that all patients with BAV have a certain degree of ascending aortopathy because they do exhibit a greater ascending aortic diameter compared with TAV patients, 1921 even when matched for variables such as sex, age, or degree or valvulopathy. 22 The distinct manifestations of BAV- versus TAV-associated aortopathy is further supported by our previous work at the tissue, cellular, and molecular levels showing distinct biomechanical properties associated with differences in extracellular matrix maturity and architecture 2327 and altered SMC response to oxidative stress 6,28 in the BAV versus TAV aortopathy.…”
Section: Discussionsupporting
confidence: 67%
“…Meanwhile, BAV-AS patients who exhibit exaggerated flow eccentricity and elevation of regional WSS could benefit from less aggressive treatment strategies including reduction aortoplasty guided by WSS mapping. It was supported by long-term follow-up studies that clinical outcomes of reduction aortoplasty might rely on the extent of localized degeneration of the aortic wall at the greater curvature, 36, 37 which was typically associated with BAV stenosis. Considering the elder age of BAV-AS patients, the less aggressive approach of reduction aortoplasty could be a surgical option for future clinical studies since it was associated with lower rate of early postoperative complications as well as shorter ICU and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Guzzardi et al has shown that regions of increased WSS, measured by 4D flow MRI in BAV patients before aortic valve repair, corresponded with extracellular matrix dysregulation and elastic fiber degeneration in resected tissue samples from the same patients 8. Tsamis et al found that BAV patients exhibit asymmetric dilatation of the greater curvature of the aorta, compared to symmetric dilatation in TAV patients, concomitant with different elastin and collagen fiber orientation between the types of valves 36. Additionally, Girdauskas et al recently determined that there was no difference in correlation patterns between functional aortic root parameters and expression of aortopathy between BAV and TAV patients with aortic dilatation and AS 9.…”
Section: Discussionmentioning
confidence: 99%
“…8 Tsamis et al found that BAV patients exhibit asymmetric dilatation of the greater curvature of the aorta, compared to symmetric dilatation in TAV patients, concomitant with different elastin and collagen fiber orientation between the types of valves. 36 Additionally, Girdauskas et al recently determined that there was no difference in correlation patterns between functional aortic root parameters and expression of aortopathy between BAV and TAV patients with aortic dilatation and AS. 9 The findings of our study indicate that these apparent contradictions may be brought about by the presence of AS, which can significantly alter and dominate aortic 3D WSS patterns irrespective of valve type.…”
Section: Impact Of Asmentioning
confidence: 99%